Clinical researchEffect of ezetimibe on lipoprotein subfraction concentrations: the role of atorvastatin pretreatment - Kalogirou, Mihalis; Tsimihodimos, Vasilis; Saougos, Vasilis; Lagos, Kostantinos; Tselepis, Alexandros D.; Elisaf, Moses (Archives of Medical Science, 2007)
Introduction: Recently published data indicate that the effect of ezetimibe on lipoprotein subfraction distribution in patients receiving statin therapy may differ substantially from that observed in patients treated with ezetimibe monotherapy. The aim of our study was to directly compare the effects of ezetimibe added to established atorvastatin treatment on lipoprotein subfractions with those obtained by ezetimibe monotherapy. Material and methods: Forty dyslipidaemic patients who failed to reach their assigned LDL-C target while on atorvastatin therapy (20 mg/day) for at least 6 months were included in the study. Ezetimibe (10 mg/day) was added to atorvastatin in all patients. The concentrations of the individual lipoprotein subfractions were determined using the Lipoprint method at baseline (prior to the addition of ezetimibe) as well as after 16 weeks of combination treatment. The changes in lipoprotein subfraction concentrations were compared with those observed in 40 age- and sex-matched statin-naïve patients receiving ezetimibe monotherapy for 16 weeks. Results: Ezetimibe administration reduced VLDL concentrations either when used as monotherapy or when added to established atorvastatin treatment. However, in contrast to ezetimibe monotherapy, which reduced the concentrations of all LDL subfractions, the addition of ezetimibe in patients receiving atorvastatin decreased LDL cholesterol values exclusively by reducing the concentrations of large, buoyant LDL subfractions. In addition, while ezetimibe monotherapy reduced mainly the concentrations of small, dense LDL subspecies, the addition of ezetimibe in patients receiving atorvastatin equally reduced the concentration of all HDL particles. Conclusions: The effect of ezetimibe on lipoprotein subfractions is significantly affected by previous atorvastatin treatment.